Hajj Service Management at the Pesisir Selatan Ministry of Religious Affairs Office - Ermiga Rahma Siska; Zulhelmi Zulhelmi (Munazzama: Journal of Islamic Management and Pilgrimage, 2026)
This study aims to analyze the services management for Hajj pilgrims at the Ministry of Religious Affairs Office in Pesisir Selatan by examining the implementation of Hajj service management encountered in service delivery. The study used a descriptive qualitative approach. Research informants were selected purposively, consisting of the Head of the Hajj and Umrah Organization Section, Hajj service staff, Hajj ritual officers, and prospective Hajj pilgrims. The finding explains that the Hajj service management function has been implemented with standard operating procedures. However, several obstacles were still found, including suboptimal planning of mobile Hajj services, limited human resources, and ineffective delivery of Hajj training materials for elderly pilgrims. The research findings indicate that the innovation of mobile Hajj service is a strategy capable of increasing access to services for communities in areas far from service centers, although it still requires strengthening in the planning and evaluation aspects. Thus, the effectiveness of Hajj service management is not only determined by the existence of SOPs, but also by the organisation's ability to adapt services to the characteristics and needs of pilgrims.